Geopotential Model of Earth - Approximation of Earth Shape, Geopotential Model Testing Methods - Robert Tenzer (Communications - Scientific letters of the University of Zilina, 2001)
Stokes’ geodynamic parameters in the expansion of the gravity potential of the Earth serve for a mathematical and physical description of an outer gravity field of the Earth, the shape and the size of the Earth. In this article, the results from testing of an accuracy of the geopotential model EGM 96 at the territory of Slovakia are published.